Elastisitas Penyerapan Tenaga Kerja di Kota Padang Tahun 2010-2013 dan 2014-2017 - Tiara Mulyani; Rahmanelli .; yudi antomi (JURUSAN GEOGRAFI FIS UNP, 2019)
ABSTRACT The study aims to determine the magnitude of employment and GRDP in the city of Padang, the level of elasticity of employment in each sector as well as the leading economic sectors of the Padang City region in 2010-2013 and 2014-2017. This type of research is quantitative descriptive. Data analysis is an analysis of the growth of employment, the level of labor elasticity and analysis of Location Quotient and Shift Share. The results of the study show that: (1) The amount of employment in the City of Padang in 2010-2013 were 16,65% and years 2014-2017 were 4,40% and growth of PDRB Padang in 2010-2013 were 8,33% and years 2014-2017 were 5,95%, (2) The level of elasticity of employment in Padang in 2010-2017 is inelastic , and (3) The leading sectors of the economy of the Padang City region in 2010-2013 and 2014-2017, the highest percentage of economic growth is the construction sector and the lowest is the processing industry. Keywords: Labor elasticity, leading sector,